Ceftriaxone-induced hemolytic anemia managed successfully in a 54-year-old woman: a case report and literature review - Zhang, Liqian; Huang, Wenfeng; Xu, Jiakai; Li, Yunxing; Zhu, Jihong (Frontiers in Pharmacology, 2025)
Ceftriaxone is widely used in clinical practice for its efficacy against infections. However, its increasing association with life-threatening immune hemolytic reactions urge clinicians to enhance recognition and maintain sharp vigilance. This report details a rare and severe case of ceftriaxone-induced hemolytic anemia (CIHA), hemodynamic instability and hemolytic crisis in a 54-year-old woman after intravenous infusion of ceftriaxone following a respiratory infection. Clinicians must promptly identify symptoms suggestive of CIHA, such as fatigue, pallor, nausea, vomiting, and trunk pain, and immediately discontinue ceftriaxone. Laboratory examination can also assist in confirming the diagnosis of CIHA. Effective management measures include rigorous monitoring of vital signs, circulatory support, respiratory support, timely blood transfusion, administration of steroid hormones, IVIG infusion as necessary, plasma exchange, and symptomatic treatment of possible complications. Even after the patient has achieved full recovery, careful consideration should be given to the choice of subsequent antibiotics to prevent recurrence of CIHA.